Inhibition of Return after Color Singletons - Heinz-Werner Priess; Sabine Born; Ulrich Ansorge (Journal of Eye Movement Research)
Inhibition of return (IOR) is the faster selection of hitherto unattended than previously attended positions. Some previous studies failed to find evidence for IOR after attention capture by color singletons. Others, however, did report IOR effects after color singletons. The current study examines the role of cue relevance for obtaining IOR effects. By using a potentially more sensitive method – saccadic IOR – we tested and found IOR after relevant color singleton cues that required an attention shift (Experiment 1). In contrast, irrelevant color singletons failed to produce reliable IOR effects in Experiment 2. Also, Experiment 2 rules out an alternative explanation of our IOR findings in terms of masking. We discuss our results in light of pertaining theories of IOR.